Analysis of Students’ Learning Problems in IPAS under the Merdeka Curriculum at SD Negeri 13 Lolong - Situmorang, Feronika; Ayunis, Ayunis; Prananda, Gingga; Efrina, Gusnita (The Future of Education Journal, 2025)
Science Integration (IPAS) under the implementation of the Merdeka Curriculum at SD Negeri 13 Lolong, Padang City. The study was motivated by the empirical issue that students often experience difficulties in understanding IPAS concepts due to monotonous teaching methods and limited learning media. A qualitative descriptive approach was employed, with the data collected through observation, interviews, and documentation. The research subjects consisted of the class teacher, the school principal, and 28 students. Data were analyzed using Miles and Huberman’s model, including data reduction, presentation, and conclusion drawing, with validity ensured through source and theory triangulation. The results revealed that students’ main problems included the lack of varied learning media, low learning motivation, and limited active participation during lessons. These issues led to passive learning activities and reduced conceptual understanding. The findings indicate that effective IPAS learning requires teachers to apply interactive and contextual learning models, utilize simple digital media, and design project-based activities that relate to students’ daily experiences. The study also emphasizes the importance of school support in providing adequate learning facilities to optimize the Merdeka Curriculum implementation.